ANALISIS PERMINTAAN DAN PENAWARAN KREDIT PERBANKAN DI INDONESIA - Dewi Lusianita; Muhammad Basir Kimin; Suhel Suhel (Jurnal Ekonomi Pembangunan, 2005)
This research is about the credits of bank especially working capital credits so the title of this research is "The analysis demand and supply credits of bank". The aim of this research are to analysis the factors of demandÂ  credits and the factors of supply credits effect to working capital credits with use the simultan regressor model and the accounts is used Two-Stage Least Squares (2 SLS). This research is supported wih theories and they are demand credits theory, supply credits theory and credit market by New Keynes theory. The result of this research are from demand credits side show that economic growing is not significant to working capital credits where as the interest rate of working capital credits is significant to working capital credits and R2 is 47,40 percent shows that 47,40 the demand of credits are effected by free variables in the model. From the supply credits side show that credits capacity, CAR and DPK are not significantÂ  to working capital credits whereas the interest rate of working capital credits is significant to working capital credits and R2 is 94,58 percent show that 94,58 percent the supply of credits are effected by free variables in the model. Because the models are used in this research simultan so from the economic growing side can be effected by working capital credits, the interest rate of working capital credits and DPK. And these three variables are not significant to the economic growing . R2 is 69,08 percent shows that 69,08 percent the economic growing are effected by free variables in the model. So before giving the credits of working capital, the bankers must know information about the crediturs. To make policy must be done carefully and this research must be continued.Keywords: working capital credits, the economic growing, the interest rate of working capital credits, credits capacity, CAR and DPK.